1986
DOI: 10.1139/m86-123
|View full text |Cite
|
Sign up to set email alerts
|

Oosporogenesis by Lagenidium giganteum: induction and maturation are regulated by calcium and calmodulin

Abstract: Induction and maturation of the sexual stage (oospores) of the facultative mosquito parasite Lagenidium giganteum (Oomycetes: Lagenidiales) are complex developmental processes regulated by calcium-dependent events. Use of developmentally synchronized cultures of L. giganteum allowed stage-specific disruption of calcium metabolism. A calcium chelator (EGTA), an ionophore (chlortetracycline), and inhibitors of the calcium-binding protein calmodulin (dibucaine, trifluoperazine, chlorpromazine) disrupted several d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…These include zinc Wnger transcription factors (Pi015704, Pi014241, and Pi005054), protein kinases (Pi003811, Pi015297), and a protein phosphatase (Pi007072). Induction of a calcium-ATPase (Pi002983) is also of interest since calcium was shown to regulate oosporogenesis in Lagenidium and Saprolegnia (Fletcher, 1988;Kerwin and Washino, 1986a). It is also notable that several proteins participate in RNA metabolism or regulation, including the Puf RNA binding protein (Pi004848), two distinct mRNA decapping enzymes (Pi011975, Pi012846), and the M24 RNAse identiWed in our previous study (Fabritius et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…These include zinc Wnger transcription factors (Pi015704, Pi014241, and Pi005054), protein kinases (Pi003811, Pi015297), and a protein phosphatase (Pi007072). Induction of a calcium-ATPase (Pi002983) is also of interest since calcium was shown to regulate oosporogenesis in Lagenidium and Saprolegnia (Fletcher, 1988;Kerwin and Washino, 1986a). It is also notable that several proteins participate in RNA metabolism or regulation, including the Puf RNA binding protein (Pi004848), two distinct mRNA decapping enzymes (Pi011975, Pi012846), and the M24 RNAse identiWed in our previous study (Fabritius et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Agar cultures from four plates (20 ml of medium per plate) from which the inoculum plug and the central 1 cm had been removed were individually homogenized in a total volume of 50 ml of water in a Polytron tissue homogenizer (Brinkmann Instruments, Inc.), and oogonia, aborted oospores, and viable oospores were counted with a hemacytometer. Viability was based on easily recognizable morphological characteristics (30,33,46).…”
mentioning
confidence: 99%
“…Palmitoleic acid added to basal growth media containing appropriate sterols induced significant oosporogenesis, while oleic acid was less effective and linoleic and linolenic acids were toxic at relatively low concentrations; however, oleic and linoleic acids added as mono-, di-or triacylglycerols produced the maximum number of oospores. Trilinolenin, arachidonic and 11,14,17-eicosatrienoic acids induced no or few oopores (95). Analysis of whole cell fatty acids confirmed that all exogenous fatty acids were taken up from the media, although saturated fatty acids were incorporated more slowly.…”
Section: Sporulationmentioning
confidence: 81%
“…Recently an exogenous requirement for specific fatty acids has been documented for the induction and maturation of the sexual oospore stage of Lagenidium giganteum, a facultative parasite of mosquito larvae (94,95). Free fatty acids and triacylglycerols containing saturated fatty acids from 14C to 20C in length induce limited numbers of viable oospores in liquid culture.…”
Section: Sporulationmentioning
confidence: 99%
See 1 more Smart Citation